A 3D printed phantom for Image Quality Assessment in Cone-beam CT. (August 2018) - O'Halloran, James; Gilligan, Paddy; Cleary, Sinead; Maguire, Susan; O'Connor, Gerald; Downy, Kirby; Kleefeld, Christoph
Abstract : Aim: The number of cone-beam scanners in use within medical, therapeutic and dental practices is increasing. Quality assurance standards require the assessment of image quality. Current phantoms are not cost effective or practical. The aim of this work was to create a practical 3D printed phantom to address the quality assurance needs of cone beam units particularly in the dental field. 3D printing has the potential to provide adaptable, reproducible, low cost phantoms for use in the field where offline access to images can be difficult. Materials and methods: A phantom was designed which adhered to the requirements as outlined by the Sedentexct Guidelines. The design was constructed using 3D printing software (Solidworks, USA) to include modules for uniformity, resolution, contrast, geometrical and Hounsfield unit accuracy. A number of models, materials and production techniques were evaluated. Results: A portable robust nylon phantom was created using selective laser sintering. Chambers in the phantom allowed filling with materials for assessment of Hounsfield units. Metal implants allowed assessment of geometric accuracy and potential artefacts. The phantom met the requirements of Sedentexct testing guidelines. The phantom assessed a cone-beam dental CT (Planmeca, Finland), an angiographic CT (Artis Q, Siemens) and a conventional CT (Sensation open, Siemens. Conclusion: 3D printed nylon phantoms can be used to assess image quality and performance in multiple types of volumetric imaging systems.